The Development of Learning Media in the Form of Pop-up Books to Understand Narrative Text - Aldiana Lakshinta Sasqia Putri; Sawitri - Retnantiti (Universitas Negeri Malang, 2020)
The purpose of this study was to develop learning media in the form of pop-up books to understand narrative text with the title Dunkelrestaurant in the book Netzwerk A2. This research and development uses the ADDIE model with 5 development stages, namely (1) needs analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The types of data in this study are quantitative and qualitative. The data were obtained from media experts, material experts, observers, and trial subjects. To collect data used instruments in the form of questionnaires and observation sheets. From the results of product validation by media experts, the product feasibility percentage is 90.9 percent, while from the material expert validation results, the product eligibility percentage is 88.8 percent. The product eligibility percentage obtained is included in the valid category, so the product is suitable for use in Deutsch II lectures at the Department of German Literature, State University of Malang. Meanwhile, the results of filling out questionnaires by students and observation sheets during the trial activity showed that the product was very interesting and helped students in understanding the text.